Oropharyngeal detection of specific gut-derived Enterobacterales is associated with increased respiratory infection risk in older adults - Miller, Sophie J.; Zhang, Frank; Taylor, Steven L.; Shoubridge, Andrew P.; Flynn, Erin; Vasil, Egi; Woodman, Richard J.; Papanicolas, Lito E.; Rogers, Geraint B. (Frontiers in Aging, 2025)
Respiratory tract infections (RTI) are a major contributor to morbidity and mortality in later life. RTI risk factors in older populations, including declining general health, altered airway physiology, and increased pharmaceutical exposures, also contribute to changes in the oropharyngeal (OP) microbiota. We sought to investigate whether such changes predict future incidence of RTI. OP microbiota characteristics were measured in 190 residents of long-term aged care. Fifty-four participants (28.4%) experienced one or more study-defined RTIs during the 12-month follow-up period, of which 28 (14.7%) occurred within 90 days of sample collection. OP microbiota composition was significantly associated with days to RTI event (F = 1.74, R2 = 1.02%, p = 0.04). Detection of Enterobacterales species (Enterobacter cloacae, Escherichia coli, Klebsiella oxytoca, Klebsiella pneumoniae, Klebsiella variicola, and Proteus mirabilis) were independently associated with RTI risk after covariate adjustment (subdistribution HR: 4.84; 95% CI: 1.65–14.19; p = 0.002). Strain-level analysis performed on metagenomes from contemporaneous OP and stool samples identified co-carriage of indistinguishable Enterobacterales strains in those with Enterobacterales-positive OP samples, suggesting intra-participant strain acquisition. We report OP carriage of Enterobacterales species to be a marker of future RTI risk in long-term aged care residents, reflecting the independent influence of common ageing-associated risk exposures.